Acoustic mapping of the back-scattering interferometer signal in a CO2 laser - Wojaczek, Dorota A.; Chodorowski, Paweł; Dobrucki, Andrzej B.; Witkowski, Jerzy S.; Pliński, Edward F. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
It is shown that a microphone placed in the laser plasma can be used for detection and observation of the optical phenomenon such as an optical feedback in a continuous wave regime of the laser operation. To observe the effect, a periodically moved external mirror has been used. The periodical changes of the optical beam intensity in the laser cavity generated changes in frequency and amplitude of the acoustic signal. In conclusion, the acoustic wave gives information about optical effects created in a waveguide CO2 laser.
Optica Applicata, Vol. 40, 2010, nr 4, s. 909-919
Keywords: optyka; CO2 laser; self-mixing; optical feedback; back-scattering; interferometer; photoacoustics